2021
DOI: 10.1371/journal.pone.0252041
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of target lesion heterogeneity for treatment efficacy assessment in late stage lung cancer

Abstract: Rationale Recent studies have discovered several unique tumor response subgroups outside of response classification by Response Evaluation Criteria for Solid Tumors (RECIST), such as mixed response and oligometastasis. These subtypes have a distinctive property, lesion heterogeneity defined as diversity of tumor growth profiles in RECIST target lesions. Furthermore, many cancer clinical trials have been activated to evaluate various treatment options for heterogeneity-related subgroups (e.g., 29 trials so far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The treatment process of mid to late-stage LC involves not only chemotherapy, molecular targeted therapy, immunotherapy, anticancer drug therapy, and nutritional therapy, but also care measures to prolong the survival time, improve QoL, alleviate pain, and prevent complications [21,22]. However, traditional care methods have limitations including the lack of continuous and personalized care support after discharge, insufficient intervention addressing sleep quality, exercise, and mental health, and the possible lack of systematic and structured care practices, which compromise the rehabilitation and QoL of patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment process of mid to late-stage LC involves not only chemotherapy, molecular targeted therapy, immunotherapy, anticancer drug therapy, and nutritional therapy, but also care measures to prolong the survival time, improve QoL, alleviate pain, and prevent complications [21,22]. However, traditional care methods have limitations including the lack of continuous and personalized care support after discharge, insufficient intervention addressing sleep quality, exercise, and mental health, and the possible lack of systematic and structured care practices, which compromise the rehabilitation and QoL of patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a lung micro nodule may be considered as NTL by one reader while the paired reader may not consider the finding significant (see example in Figure 8 ) which could potentially lead to a discrepancy in evaluating the extent of disease. Indeed, during the follow-up, some of the differences between readers in capturing disease progression have been explained by possible dissociation of the response i.e., when tumors selected from different disease locations respond differently to treatment ( 24 , 25 ). In trials evaluating the efficacy of immunotherapy, a dissociated response has been reported in 30% of patients for our indication ( 26 ).…”
Section: Discussionmentioning
confidence: 99%